Mutations in BRCA2 and taxane resistance in prostate cancer - Nientiedt, Cathleen; Heller, Martina; Endris, Volker; Volckmar, Anna-Lena; Zschäbitz, Stefanie; Tapia-Laliena, María Angeles; Jäger, Dirk; Schirmacher, Peter; Sültmann, Holger; Stenzinger, Albrecht; Hohenfellner, Markus; Grüllich, Carsten; et al. (Scientific reports, 2017)
Mutations in BRCA1 or BRCA2 define a subset of prostate cancer patients. Herein, we address the question whether BRCA1/2 mutations have a predictive impact on chemotherapy with docetaxel, a widely used drug in patients with metastatic castration resistant prostate cancer (mCRPC). Fifty-three men treated with docetaxel for mCRPC were tested for somatic BRCA1/2 mutations of the primary tumor. In a subgroup of patients, BRCA1/2 protein expression was tested as a potential surrogate marker for BRCA1/2 inactivation. Eight of 53 patients (15.1%) harbored a deleterious BRCA2 mutation. No BRCA1 mutation was found. Patients with a BRCA2 mutation showed a response rate of 25% to docetaxel in comparison to 71.1% in men with wildtype BRCA2 (p = 0.019). While the time to develop castration resistance was similar in both subgroups, the overall survival was significantly shorter in patients harboring a BRCA2 mutation. No correlation between the BRCA1/2 protein expression and the response to docetaxel was found. While the presence of a BRCA2 mutation does not preclude a response to docetaxel, there is overall a significant correlation between BRCA2 inactivation and a poor response rate. Our results suggest that a close oncological monitoring of patients with BRCA2 mutations for taxane resistance is warranted.
Gesehen am 09.10.2018
Im Titel ist "BRCA2" kursiv geschrieben